A Look at Informal Logic - Iryna Khomenko (International Society of Philosophy and Cosmology, 2018)
The challenges of the global time require new solutions and up-to-date ways of thinking and communication. These challenges call for the ability to use critical thinking to face the ever-changing world and the ability to maintain a dialog based on the effective skills of communication. Studies in the fields of logic and argumentation theory are of particular importance in this regard. Nowadays they can be presented as a mix of theoretical and practical approaches. In this paper, I will present my reflections on informal logic, which was formed in the late 1970s. Unfortunately, in spite of numerous papers, books, and text-books published over the last forty years, consensus on many issues in this field has not been achieved so far. Therefore, it is difficult to treat informal logic as one of the well-defined approaches to argumentation. The goal of this paper is to take a look at the place of informal logic in state-of-the art study of argumentation by clarifying its subject matter and figuring out the realm to which informal logic belongs.